1997
DOI: 10.1177/0310057x9702500610
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Pethidine: An Alternative Anaesthetic for Transurethral Resection of Prostate?

Abstract: We aimed to determine the usefulness of intrathecal pethidine as the sole anaesthetic for transurethral resection of prostate (TURP) while comparing the incidence of hypotension with intrathecal bupivacaine. A double-binded randomized prospective trial was conducted involving 40 patients for TURP. The patients were divided equally into two groups; group A received 2 ml 0.5% bupivacaine intrathecally and group B received 40 mg pethidine intrathecally. Changes in blood pressure and heart rate were measured over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A number of clinical and experimental studies (10 -22) have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable in effect to lidocaine. In medicine, it has been administered intrathecally (8,10,14,16,18), spinally (13,20), and as a saddle block (11), as well as locally for intravenous regional anesthesia (21), block (15), and infiltration (22) for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…A number of clinical and experimental studies (10 -22) have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable in effect to lidocaine. In medicine, it has been administered intrathecally (8,10,14,16,18), spinally (13,20), and as a saddle block (11), as well as locally for intravenous regional anesthesia (21), block (15), and infiltration (22) for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%